Development of Meaningful Learning Scale (MeLearn) - Ghazali, Norliza; Mustakim, Siti Salina; Nordin, Mohamad Sahari (Innovare Academics Sciences, 2020)
In the 21st century educational landscape, a meaningful learning environment is important. Meaningful learning encourages dynamic students’ involvement in learning. Nevertheless, the dearth of the scholarly literature of measurement for meaningful learning has been found. Hence, this study proposes to develop and validate a meaningful learning scale (MeLearn). The study conceptualized meaningful learning in five dimensions. An Exploratory Factor Analysis (EFA) is used to expose the appropriate items for MeLearn as well as validity and reliability. The current study chose the cross-sectional research design, while the data was collected from 289 university students, using a structured survey. This study finalized MeLearn to thirty-one (31) items yielding five (5) dimensions, i.e., cooperative learning (7 items), active learning (5 items), authentic learning (6 items), constructive learning (6 items) and intentional learning (7 items). The eigenvalues of the five dimensions of MeLearn fell within 1.17 and 12.21 with the total variance explained is 51.9 %. The reliability indexes ranged from 0.838 to 0.885. The rigorous development procedure and analysis of MeLearn have warranted that the scale is reliable and valid. The research provides insightful information about the dimensions and items of meaningful learning scale which can be interpreted more easily and meaningfully.